Parents Perspective on Translation Quality of Children Bilingual Storybooks - Dina Maharani; Chusna Apriyanti; Agustina Sri Hafidah (International Journal of English and Applied Linguistics (IJEAL), 2021)
Parents believe that bilingual storybooks for children can be used as media for children in learning English. However, not all bilingual books have good quality in their translation. This research aims to know the parents’ perspective on the quality of translation in children’s bilingual storybooks. This is descriptive quantitative research. The data were gathered by using a questionnaire through implementing Google Form for 52 parents as respondents. Some considerations in choosing the respondents were applied, such as the parents have kindergarten and elementary schools level students and the parents use bilingual storybooks at home. The storybooks in this research consist of English and Indonesia, with Bahasa Indonesia as the source language and English as a target language. The research was conducted from April to June 2021. After being collected, the data are presented as the data display stage, and the researchers conclude. The result shows that there are 48 parents of 52 parents who consider bilingual storybooks as media.  Fifty parents also buy bilingual storybooks for their children. Among the respondents, 37 parents check the language of the books, and 15 parents do not match. Forty-two parents believe that the books are qualified for learning English. There are five considerations for parents in buying books: story, picture, language, price, and publishers/authors.